2010
DOI: 10.1210/jc.2009-2262
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Function, But Not Carotid Intima-Media Thickness, Is Affected Early in Menopause and Is Associated with Severity of Hot Flushes

Abstract: Impairment of endothelial function is present in the early menopausal years, whereas carotid IMT is not affected. Severity of hot flushes is the main determinant of endothelial dysfunction in early menopausal women. The studied ER polymorphisms do not offer important information on vascular health in early menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 35 publications
3
78
2
3
Order By: Relevance
“…Endothelial function was assessed in all participants by measurement of endotheliumdependent vasodilation in the right brachial artery in response to hand hyperemia, based on previously described methodology (20), according to recently published recommendations in children and adolescents (7). Images were acquired at baseline and every 30 seconds from the first to the third minute after deflation of a wrist cuff inflated to ϳ250 mm Hg for 4 minutes for measurement of FMD.…”
Section: Vascular Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial function was assessed in all participants by measurement of endotheliumdependent vasodilation in the right brachial artery in response to hand hyperemia, based on previously described methodology (20), according to recently published recommendations in children and adolescents (7). Images were acquired at baseline and every 30 seconds from the first to the third minute after deflation of a wrist cuff inflated to ϳ250 mm Hg for 4 minutes for measurement of FMD.…”
Section: Vascular Studiesmentioning
confidence: 99%
“…Common carotid artery (CCA) IMT measurement was performed in all participants using a standardized protocol published previously (20), based on recently published recommendations in children and adolescents (7). Three consecutive longitudinal images of each CCA 1-2 cm proximal to the bifurcation were acquired.…”
Section: Vascular Studiesmentioning
confidence: 99%
“…Emerging evidence suggests that VMS and cardiovascular risk are related, possibly through inflammation, endothelial dysfunction, 3 or activity of the sympathetic nervous system. 4 The directions of the relationships are unclear, however.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that women with VMS have less favourable cardiovascular markers than those reporting no symptoms. [5][6][7][8] Other studies have reported reduced endothelial function, 3,9 increased intima media thickness (IMT), 10 and coronary artery calcifications (CAC), 11 among women with hot flushes. In another study, however, hot flushes were not significantly associated with blood pressure, 12 endothelial function, 13 or lipids and inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%
“…Satoh and Ohashi (2005) reported that 19.7% of women believe that menopausal symptoms are not symptoms of a sickness and prefer to wait until the menopausal symptoms disappear. Various studies showed that women with severe menopausal symptoms have risks of a decrease in vascular function and insulin resistance in the future (Thurston et al, 2012;Bechlioulis et al, 2010). During health examinations, physicians and/or nurses or nurse practitioners can provide information on appropriate treatments and make appropriate referrals for advanced care as needed.…”
Section: Discussionmentioning
confidence: 99%